Intraocular Foreign Bodies: Clinical Characteristics and Factors Affecting Visual Outcome - Yanyan Liang; Shuang Liang; Xiaoli Liu; Danyan Liu; Jialiang Duan (Journal of Ophthalmology)
Objective. To investigate the clinical characteristics and factors affecting visual outcome in patients with intraocular foreign bodies (IOFBs) and determine the risk factors for the development of endophthalmitis. Study Design. A retrospective case-series study design was adopted. Subjects. In total, 242 patients (242 eyes) who were hospitalized and underwent surgical treatment for IOFB at the Second Hospital of Hebei Medical University between January 1, 2008, and December 31, 2019, were included. Methods. The demographic data, cause of injury, characteristics of IOFBs, postinjury ocular manifestations, and surgical details of the subjects were collected, and the factors affecting visual outcome and endophthalmitis development were analyzed. Results. The most common cause of IOFBs was the propulsion of foreign bodies into the eye due to hammering (149 cases, 61.57%), followed by foreign body penetration (57 cases, 23.55%). Most of the subjects were young adult men who sustained injuries in the work environment. Poorer visual outcomes were found in subjects with initial presenting symptoms visual acuity (PVA) < 0.1, largest IOFB diameter ≥ 3 mm, IOFBs located in the posterior segment, wound length > 5 mm, entrance wound length larger than the largest IOFB diameter, concomitant retinal detachment, concomitant vitreous hemorrhage, concomitant endophthalmitis, and concomitant proliferative vitreoretinopathy (PVR). Factors related to the development of endophthalmitis included lens capsule rupture, time of stage 1 repair surgery ≥ 24 h after trauma, removal of IOFBs ≥ 24 h after trauma, and nonadministration of intravitreal antibiotic injection. Conclusion. Among patients with IOFBs, initial PVA < 0.1, entrance wound length larger than the largest IOFB diameter, concomitant endophthalmitis, and concomitant PVR were risk factors for poor visual outcomes. Lens capsule rupture was a risk factor for endophthalmitis development, and the administration of intravitreal antibiotic injection was a protective factor against endophthalmitis development.